2016
DOI: 10.1097/igc.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hematopoietic Growth Factors on Blood Transfusion Needs, Incidence of Neutropenia, and Overall Survival Among Elderly Advanced Ovarian Cancer Patients Treated With Chemotherapy

Abstract: Erythropoietin-stimulating agents were effective in reducing blood transfusion need. Granulocyte colony-stimulating factors were effective in lowering neutropenia incidence and also were associated with improved survival in elderly ovarian cancer patients. Findings are consistent with clinical trials and clinical guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…An analysis from the Surveillance, Epidemiology, End Results database showed that erythropoietin-stimulating agents and granulocyte colony-stimulating factors were effective and improved OS in elderly EOC patients. 31 In the present series, approximately 20% of the patients received supportive care during chemotherapy.…”
Section: Discussionmentioning
confidence: 73%
“…An analysis from the Surveillance, Epidemiology, End Results database showed that erythropoietin-stimulating agents and granulocyte colony-stimulating factors were effective and improved OS in elderly EOC patients. 31 In the present series, approximately 20% of the patients received supportive care during chemotherapy.…”
Section: Discussionmentioning
confidence: 73%
“…Both CSFs and ESAs are commonly used to prevent infection and neutropenia in patients receiving chemotherapy and for the treatment of asthenia by stimulating the growth of red blood cells, respectively (115-117). The use of CSFs and ESAs results in better cancer patient adherence to chemotherapy without a reduction in dose administration, thus improving the clinical outcomes of the therapy (118,119).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Supporting this model, the present results showed that type II EOC was more common in elderly women than in younger patients. The extremely poor prognosis of elderly EOC may be due to different tumor biological characteristics, discrepancies in clinical practice, and skewed distribution of clinicopathological characteristics [39,[47][48][49][50][51]. Advanced age was associated with prognosis after the influences of FIGO stage, histological type, and even the surgical outcome were excluded in the type II EOC patients who received optimal debulking, although the independence has been demonstrated by previous studies [15,24].…”
Section: Discussionmentioning
confidence: 95%